Pengembangan Bahan Ajar Flipbook Brebasis RADEC pada Mata Pelajaran Pendidikan Pancasila di Kelas V Sekolah Dasar Kota Padang - Suherman, Dwi Athana; Wulandari, Fikhen Tri; Mansurdin; Ladiva, Hasmai Bungsu (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Pancasila Education learning in elementary schools still faces limitations in the use of interactive digital teaching materials and is able to encourage active student involvement. This study aims to develop valid, practical, and effective RADEC-based Flipbook teaching materials for Pancasila Education learning in fifth grade elementary schools. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The study was conducted at SDN 02 Indarung, SDN 12 Padang Besi, and SD Semen Padang. Product validity was assessed by material, language, and media experts, while practicality was measured through teacher and student responses. Effectiveness was analyzed based on the increase in learning outcomes through a comparison of pre-test and post-test using N-Gain. The results showed that the RADEC-based Flipbook teaching materials obtained a validity of 93% with a very valid category, teacher practicality of 95.83%, and student practicality of 92.44% with a very practical category. The average N-Gain value of 0.776 indicates high effectiveness. Thus, the RADEC-based Flipbook teaching material is suitable for use in supporting interactive Pancasila Education learning that is oriented towards active student involvement.